Effect of solutionizing and aging on the microstructure and mechanical properties of powder bed binder jet printed nickel-based superalloy 625. (5th December 2016) - Mostafaei, Amir; Behnamian, Yashar; Krimer, Yuval L.; Stevens, Erica L.; Luo, Jing Li; Chmielus, Markus
Abstract: In this study, the influence of solutionizing and aging treatments on the microstructure and mechanical properties of alloy 625 superalloy samples produced by powder bed binder jet printing was investigated. Vacuum melted argon atomized 625 superalloy powder was used to fabricate green parts. Samples vacuum sintered at 1280 °C for 4 h to optimize density to 99.6% were subjected to solution and aging treatments at 1150 °C for 2 h and 745 °C for 20 h and 60 h, respectively, in order to improve microstructure and mechanical properties. Elemental analysis, phase formation and microstructure of the sintered, solution treated and aged samples were investigated by using optical, scanning/transmission electron microscopy with electron dispersive spectroscopy, and X-ray diffraction. The results indicate that the aging treatment resulted in the formation of intermetallic phases such as Ni3 Nb and Ni2 (Cr, Mo) as well as carbides such as NbC, Cr23 C6 in the microstructure. While the microhardness and tensile strength of the aged specimen increased due to these phases, the ductility value decreased. This study shows that alloy 625 produced by binder jet printing subjected to aging treatments has comparable properties to cast alloy 625. Graphical abstract: Highlights: Near full dense sample is achieved by powder bed binder (BJP) jet printed alloy 625. Microstructure of differently heat treated BJP alloy 625 were studied. Precipitation and phase evolution were studied using XRD, TEM, and elemental analysis. Tensile strength of 697 MPa, elongation of 36% and hardness of 320 HV were achieved for aged conditions.